Trends in consumer behaviour and accommodation choice: perspectives from India - Shah, Chetan; Trupp, Alexander * (Routledge, 2020)
This research analyses tourist’s characteristics and accommodation choice in Nainital, a renowned British-era hill station in India. Questionnaires were administered to a convenience sample of 200 visitors at tourist host-spots. Descriptive and factorial statistics reveal five principal factors that motivate and influence visitors’ accommodation preferences. The majority of respondents chose accommodation on the outskirts of Nainital and cottages or stand-alone villas. Findings suggest that Nainital has become a lower-middle-income destination for domestic tourists whereas one-day visitors have been identified as an emerging trend in hill station tourism. Findings offer insights into changing trends of tourism and target markets in the hill stations of India, and provide direction in shaping facility, service and marketing decisions of hoteliers.